Problems of Setting the Pricing Policy of an Enterprise - Krzeszowski, Wojciech Dawid (Problemy kształtowania polityki cenowej przedsiębiorstwa, 2010)
The issue of setting the pricing policy is very complex and very often it is highly difficult to definitively set the level of prices. No single universal solution can be put forward here because each case requires an individual approach and consideration of many factors. The policy of price setting requires a continuous co-operation of the sales and marketing and financial departments. Considerations in this area should be made continuously and from a wide perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 65-74
Keywords: pricing policy; profitability; price setting